Tindak Pidana Korupsi oleh Oknum Partai Politik dan Pertanggungjawaban Pidananya - Zamzimi, Padlan (Universitas Batanghari Jambi, 2025)
This research aims to determine the criminal responsibility of political parties for criminal acts of corruption. The research method used is normative juridical. The results of the research reveal that the criminal responsibility of political party individuals for criminal acts of corruption is Article 20 Paragraph (l) and (2) of Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Corruption Crimes. Penalties that can be imposed on individuals from political parties who are proven to have legally committed criminal acts of corruption, if the political party is considered a corporation and it can be proven that there is a flow of funds into the political party's coffers through the Financial Transaction Reports and Analysis Center (FTRAC). Dissolution of political parties as an additional form of punishment can be carried out. Regarding the authority of two judicial institutions to dissolve political parties, the two judicial institutions can do the same thing for different reasons or other options, namely the division of authority where the criminal justice system is only a recommendation considering that the penalty for freezing or dissolving a corporation is only an additional penalty, whereas freezing or dissolving remains the authority of the Constitutional Court.